A Model of Consumptive Behavior in Fintech Paylater Users: Testing Financial Attitude and Self-Control with Locus of Control as a Moderating Variable - Munir Nur Komarudin; Rina Masruroh; Wely Hadi Gunawan; Hamdan Danial (IJSM, 2026)
This study examines the effect of financial attitude and self-control on consumptive behavior among fintech PayLater users and analyzes the moderating role of locus of control. A quantitative approach was employed using primary data collected through questionnaires, with analysis conducted using multiple regression and Moderated Regression Analysis (MRA).The results show that financial attitude and self-control have a negative and significant effect on consumptive behavior, indicating that better financial attitudes and higher self-control reduce consumptive tendencies. However, the relatively low coefficient of determination suggests that other factors outside the model also influence consumptive behavior.Moderation analysis reveals that locus of control does not moderate the relationship between financial attitude and consumptive behavior, but significantly moderates the relationship between self-control and consumptive behavior. This indicates that individuals with a stronger internal locus of control are more effective in utilizing self-control to suppress consumptive behavior. Thus, locus of control functions as a selective moderator, strengthening behavioral control rather than cognitive financial attitudes. The novelty of this study lies in integrating cognitive, psychological, and personality dimensions in the context of fintech PayLater. Practically, reducing consumptive behavior requires not only improving financial attitudes but also strengthening self-control and internal locus of control.